"A designer baby? Yeah, right." In-vitro fertilization in Jodi Picoult's My Sister's Keeper. (November 2019) - Michailidou, Artemis
Abstract: The following paper is going to focus on one of the most popular, yet least examined contemporary US authors, Jodi Picoult. Taking as my starting point her well-known novel My Sister's Keeper (2004), I will explore in-vitro fertilization (IVF) and the concept of the "designer baby". After presenting an overview of feminist scholarly work on this controversial subject, I will examine Picoult's own approach to reproductive technologies in the 21st century, and draw attention to the instrumental role of IVF in the re-configuration of gender and family structures. Ultimately, I will argue that My Sister's Keeper raises crucial questions about biology, morality and ethics in contemporary America, and sensitively problematizes the way reproductive health is politicized today.